IMPLEMENTASI PROGRAM LITERASI KOLABORATIF DALAM MENDUKUNG PEMBERDAYAAN MASYARAKAT DESA BONJERUK - Hakti, Mualan Tunandar; Putra, Galih Wirabhakti Widhiantara; Krowin, Enrique Suban Putra Damian; Mahardini, Haulia; Deedat, Syach; Nabila, Nabila; Safitri, Rizki; Pendika, Kinanta Arseti Marga; Sari, Sri Maunanda; Sanobadi, Ihwan; Ngudiyono, Ngudiyono (Universitas Mataram, 2025)
The collaborative literacy program is a strategic effort to improve the quality of education and community empowerment through synergy between schools, Community Reading Gardens (TBM), village government, and student community service programs (KKN). This program was implemented in Bonjeruk Village, Jonggat District, Central Lombok Regency for 45 days, involving the Girang Bace TBM, elementary schools, and the village community. The implementation method used a descriptive qualitative approach through observation, participatory education, and mentoring children in creative literacy activities such as reading aloud, retelling, book reviews, reading-based projects, and literacy and arts competitions. Results showed an increase in children's interest in reading, reading comprehension skills, and the children's courage to express their opinions publicly. Furthermore, the community began to actively participate in supporting village literacy facilities. The collaborative literacy program has proven effective in creating a sustainable literacy ecosystem, strengthening a reading culture, and contributing to human resource development in Bonjeruk Village.